Rapid Application Development with OutSystems : Create applications with OutSystems up to seven times faster than with traditional technologies /: Create applications with OutSystems up to seven times faster than with traditional technologies. (2022) - Pereira, Ricardo; Moreira, Paulo
No abstract available